(untitled) (Numerus academy review, 2026)
In This study, our interest will be focused the most important condition in which aged people live in Tunisia, as well as their relation to the challenges made by the population ageing (In Tunisia). Currently, these conditions will give a sense to senility. As part, of this work, the analyses will involve two phases: - First, we will make on observation on the living condition of the aged people in Tunisia. - Second, we will try to consider / to examine the most important challenges mode by population ageing on the national level.